Device Accomplishing and Testing with Ball On Cylinder Lubricity Evaluator (BOCLE) - GIFRY (NIM 13103120), RIZWAN
Ball On Cylinder Lubricity Evaluator (BOCLE) is one of the fuel lubricity test device that can simulate wear phenomenon caused by sliding wear which occurs in machine components, especially fuel pump. The phenomenon is simulated by the friction of 0.5 inch ball specimen on 1.75 inch rotated cylinder drowns in fuel test. The purpose of this final project researching humidity effects on wear using the BOCLE device, which accomplished by making the humidity air-conditioner equipment to control the relative humidity of process air. The air relative humidity level of this research is 1%, 10%, 20%, 30%, 40%, 50%, 60%, and 70%. The humidity air-conditioner consists of dehumidifier and humidifier. Dehumidifier is made with the mixture of dry air and ambient air using silica gel and molecular sieve 4A as the absorbent. The air mixture is controlled to resulting the 1%, 10%, 20%, 30%, 40%, and 50% relative humidity. The humidifier is made with the mixture of ambient air and wet air which produced by the air-sprayer. The air mixture is controlled to resulting the 60% and 70% relative humidity. The test result shows that there is no trend of humidity effects on boundary lubrication wear. In this case the lubricant is diesel fuel. The small difference temperature of test fluid makes a little changes of viscosity, therefore the correlation between wear and friction is quite dominant. The 10% humidity results the smallest wear, where at 1% and 40% relative humidity results wear value out of ASTM D 5001 standards. Therefore, choosing 10% relative humidity at the test is correct, because it is cause the smallest wear value.